Faculty Development Series on Assessment in Graduate Medical Education: Patient Care Skills - Heather Burrows; David Rappaport (Association of American Medical Colleges, 2014)
Abstract Introduction This resource is a set of PowerPoint slides that were designed for the purpose of faculty development. The slides are intended for presentation by a residency program director (or designee) in a didactic or workshop setting for the purpose of enhancing the faculty's ability to assess Patient Care Skills in trainees. This presentation is the third in a six-part series that was commissioned by the Program Directors Committee of the American Board of Pediatrics based on their publication entitled Assessment in Graduate Medical Education: A Primer for Pediatric Program Directors. All presentations in this series were developed through collaboration with the primary authors of the publication. Methods This case-based presentation begins by defining the competency of Patient Care Skills, then explores various assessment tools available for evaluating learners in this competency. The presentation introduces the concept of The Pediatrics Milestone Project and demonstrates how milestones can be used to better assess Patient Care Skills. The presentation concludes with a series of case studies where the participants are asked to assess the performance of the learners in the case studies. Speaker's notes are provided at the bottom of the slides to enable the presenter to have a deeper understanding of the content. The presentation requires 45-60 minutes to present in its entirety, but can be abbreviated or expanded as needed. Results This presentation has been presented by the two authors (Burrows and Rappaport) to their own faculty. The presentations were well received in each setting generating robust discussion. Faculty expressed improved understanding of the competency, assessment tools, and the Pediatric Milestones. Faculty participated in assessment of each of the case scenarios using traditional and Milestones-based tools. Faculty also made several suggestions regarding how the program can modify existing evaluation tools to better assess this competency. Discussion These slides are the second in a series that was developed for use by Pediatric Program Directors for use in faculty development around milestone-based assessment.